The UX Book : Process and Guidelines for Ensuring a Quality User Experience. - Hartson, Rex (Elsevier Science, 2012)
This is a comprehensive textbook on designing interaction to ensure a quality user experience. Combining breadth, depth, and practical applications, this book takes a time-tested process-and-guidelines approach that provides readers with actionable methods and techniques while retaining a firm grounding in HCI concepts and theory. The authors will guide you through the UX lifecycle process, including contextual inquiry and analysis, requirements extraction, design ideation and creation, practical design production, prototyping, and UX evaluation. Development activities are linked via handoffs.